Effects of Uro-Vaxom vs. placebo on the urinary tract microbiome in individuals with spinal cord injury in a randomized controlled pilot trial (Uro-Vaxom pilot) - Ezra Valido; Alessandro Bertolo; Jens Wöllner; Jürgen Pannek; Jörg Krebs; Jivko Stoyanov (Scientific Reports)
Abstract Individuals with spinal cord injury/disease (SCI/D) have a high incidence of urinary tract infections (UTI). This randomized controlled pilot trial investigated the effect of an immunomodulator (Uro-Vaxom) versus a placebo on the urinary tract microbiome of individuals with SCI/D to inform the design of a larger trial. Twenty participants with SCI/D undergoing primary rehabilitation were randomized to receive either Uro-Vaxom or a placebo for three months (ClinicalTrials.gov NCT04049994 08/08/2019). Urine was collected at baseline, immediately post-treatment, and three months post-treatment. DNA was extracted and sequenced using full-length 16 S rRNA using Oxford Nanopore technology. Internal controls were added for absolute abundance estimation. There were 10 participants in Uro-Vaxom and 10 in placebo analyzed. The prevalence of Escherichia coli was lower in the Uro-Vaxom group (2/10) compared to the placebo group (5/10) post-treatment, although this difference was not statistically significant. Significant alpha and beta diversity differences were associated with the microbial load, sex, and voiding method. Uro-Vaxom showed potential in reducing E. coli prevalence during the treatment period, but this result requires validation in a larger trial. Future trials should consider the baseline microbial load and optimal timing of intervention to ensure that the observed effects are attributable to immunomodulation.